Nuclear genome size and karyotype analysis in Papaver for BAC library construction - Kyrylenko, T.K.; Martynenko, O.I.; Alkhimova, O.G. (Біополімери і клітина, 2005)
The objective of the research carried out is study of the pathway of alkaloid production in Papaver species and cell lines, and integration data on physical mapping of newly developed marker DNA sequences with existing difference in expression of genes for key enzymes of alkaloid biosynthesis. This research requires the knowledge on genome structure and organization, and development of genomic resources for detailed characterization of opium poppy genome. The work is focused on the investigation of some features of genome organization of Papaver somniferum and related species, Papaver bracteatum and Papaver rhoeas. These characteristics are necessary for the construction of a BAC library which would be used as appropriate genomic resource for characterization of karyotype changes in poppy stocks with altered alkaloid biosynthesis pathway. Some of these stocks (cell lines) were generated and differed in the types of alkaloids they accumulated.